Accounting Information System of the Seventh-Day Adventist Schools in the Philippines: A User's Perception - Ruhupatty, LeRoy Tim (JBE (Journal of Business and Economics); Volume 8 No.2, 2009 JBE UNKLAB, 2009)
This paper seeks to find out whether the Accounting Information System (AIS) of the Seventh-day Adventist (SDA) Church-owned and operated secondary schools in the Philippines have kept-up with changes in Information Technology (IT), management's information need, and organization's growth. - This paper also seeks to assess the system's ability to meet its objectives. It was found that the SDA secondary schools' AIS is able to meet its objectives, have the characteristics of a successful AIS, and is responsive to changes in IT, management's information need, and organization's growth.